Internet of vehicle's resource management in 5G networks using AI technologies: Current status and trends - Nada M. Elfatih; Mohammad Kamrul Hasan; Zeinab Kamal; Deepa Gupta; Rashid A. Saeed; Elmustafa Sayed Ali; Md. Sarwar Hosain (IET Communications)
Abstract The Internet of Vehicles (IoV) and Vehicle‐to‐Everything (V2X) concept have emerged from IoT technology, which refers to connecting many vehicles with various applications to the internet. The 5G new radio is based on a cloud‐radio access network (CRAN), considered as the communication infrastructure for IoV. However, due to the significant challenges and issues, researchers have been working on IoV and V2X. One of the main challenges for V2X is resource allocation and management for a high‐speed vehicular environment. This paper discusses and provides complete detail for resource allocation and management for IoV over 5G RAN networks focusing on artificial intelligence techniques. The paper also presented reviews on integrating the multi‐layers of vehicular network architecture with AI strategy to identify advancement and future directions for resource allocation and management issues.